2022
DOI: 10.1111/acer.14785
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral characterization of withdrawal following chronic voluntary ethanol consumption via intermittent two‐bottle choice points to different susceptibility categories

Abstract: Background Alcohol is among the most commonly abused drugs worldwide. Cessation of chronic alcohol consumption can result in the appearance of withdrawal symptoms that commonly promote relapse in individuals with alcohol use disorder (AUD). Thus, preclinical models of voluntary alcohol consumption, in which animals manifest spontaneous signs of withdrawal after alcohol cessation, can be useful for studying AUD and its treatment. The intermittent two‐bottle choice paradigm (I2BC) has been used extensively to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Given the well-documented interactions between alcohol and the opioid system (Arias & Kranzler, 2008; Berrettini, 2013; Gianoulakis, 2001; Gianoulakis et al, 1989; Job et al, 2007; Oslin, Berrettini, & O’Brien, 2006), we next wanted to assess alcohol use risk in offspring maternally exposed to morphine. The offspring tested in the battery of behavioral tests during adolescence were allowed to mature into adulthood and were then evaluated in an ethanol intermittent two-bottle choice (I2BC) paradigm (Figure 6a), which has been used to assess voluntary ethanol intake (Carnicella et al, 2014; Hwa et al, 2011; Quijano Cardé & De Biasi, 2022; Quijano Cardé et al, 2021). A three-way ANOVA revealed a main effect of sex where female mice (regardless of treatment) drank significantly more ethanol than male mice, so data and analyses are presented separately for each sex.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the well-documented interactions between alcohol and the opioid system (Arias & Kranzler, 2008; Berrettini, 2013; Gianoulakis, 2001; Gianoulakis et al, 1989; Job et al, 2007; Oslin, Berrettini, & O’Brien, 2006), we next wanted to assess alcohol use risk in offspring maternally exposed to morphine. The offspring tested in the battery of behavioral tests during adolescence were allowed to mature into adulthood and were then evaluated in an ethanol intermittent two-bottle choice (I2BC) paradigm (Figure 6a), which has been used to assess voluntary ethanol intake (Carnicella et al, 2014; Hwa et al, 2011; Quijano Cardé & De Biasi, 2022; Quijano Cardé et al, 2021). A three-way ANOVA revealed a main effect of sex where female mice (regardless of treatment) drank significantly more ethanol than male mice, so data and analyses are presented separately for each sex.…”
Section: Resultsmentioning
confidence: 99%
“…if locomotion is changed then that might influence time spent in a particular zone and affect anxiety-like measures). Similar to O'Neal et al (2020) andQuijano Cardé et al (2022), z-scores were calculated for each behavioral measure. Briefly, the group mean (µ 1 ) for each behavioral measure was subtracted from the raw individual value (x 1 ) for each offspring for that behavior, and then divided by the group standard deviation, (…”
Section: -Adolescent Baseline Behavioral Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the results of previous work on the affective behavioral consequences of chronic alcohol abstinence in C57BL/6J mouse models are variable as to time into abstinence tested and paradigms utilized, as well as highly male-dominated (16). Many studies have shown that males show increased avoidance, anhedonia, and compulsive behaviors in early abstinence (>1 week) following chronic alcohol across vapor inhalation (34)(35)(36)(37)(38)(39), continuous access (21,40), intermittent drinking (13), and DID (18,22,41,42). Behavior during protracted abstinence (<1 week) in males is somewhat variable, with increased avoidance following chronic vapor (17) and DID (15,18), with no effects following continuous (20,21) and on most measures during intermittent access (10), and fairly consistent increased anhedonia across alcohol vapor (17,19) and continuous drinking (20,21,40), with some exceptions for DID (18,23).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the complexities of binge drinking behavior remain poorly understood in females, including in rodent models such as the commonly used C57Bl/6J mouse strain that has been employed robustly in males. In particular, it is unclear whether females consume more than males due to differences in alcohol preference or motivated voluntary consumption, as the studies performed to date report a mix of results showing elevated female preference for at least some time points of alcohol exposure (10,11) or no sex differences (9,(13)(14)(15), depending on the alcohol exposure paradigm and length.…”
Section: Introductionmentioning
confidence: 99%